"I'll donate money today and time tomorrow": The moderating role of attitude toward nonprofit organizations on donation intention. Issue 3 (12th September 2019) - Song, Doori; Kim, Dong Hoo
Abstract : Across two experiments, this study provides support for the concept that money and time are marked by psychologically distinct constructs. As temporal distance increases, preferences are more likely to be based on the value associated with a high‐level construal of options than the value associated with a low‐level construal of options. That is, as potential contributors are asked to donate later, high‐level featured resources (i.e., time) take focal precedent over low‐level ones (i.e., money) in judging preference for donation methods. This study also found that the match effect between temporal distance and construal level holds only when the level of attitude toward nonprofit organization (NPO) is relatively favorable. However, donation intention is enhanced under mismatch conditions when the level of attitude is less favorable. That is, when potential contributors hold relatively less favorable attitudes toward the NPO, those who are requested to make an expediting decision of donation are more likely to have higher intention to donate with a high‐level construal resource. This study attributed the finding to the shift of people's focal resource through their level of attitude toward the NPO.